The e-learning perceptions of nursing students during the COVID-19 pandemic: a mixed-method systematic review: Nursing students and e-learning - Mazzotta, Rocco; Bressan, Valentina; Maurici , Massimo; Alvaro, Rosaria; Bulfone, Giampiera (Acta Biomedica Atenei Parmensis, 2024)
Background and Objective: Governments around the world implemented lockdown measures to flatten the pandemic curve of COVID-19 and, as a result, schools, colleges and universities in the highly contagious areas of the world closed and shifted from face-to-face learning to online methodologies. The rapid change in teaching methodology introduced many health professional students to different approaches to learning which can be used anywhere and at any time. The aim of this study is to analyze nursing students’ perceptions of e-learning during the COVID-19 pandemic. Methods: A mixed-methods systematic review was conducted. We considered PubMed, CINAHL, Scopus, Eric and Business Source Complete. All empirical peer-reviewed studies were included if they investigated perceptions of e-learning education of nursing students during the COVID-19 pandemic, with quantitative, qualitative or mixed-methods design, published between 2020 and June 2022 in English or Italian. The extracted data were combined using a data-based convergent synthesis approach. Results: A total of 11 studies were selected. Four themes emerged: promoting valuable learning, challenging experiences and critical perceptions, using online learning in the future and elements affecting e-learning effectiveness. Conclusions: This review has explicit and practical recommendations for universities to make advancements in their digital systems not only for students’ use but also for teachers.